2023
DOI: 10.1037/spq0000516
|View full text |Cite
|
Sign up to set email alerts
|

Understanding African American vernacular English and reading achievement: Implications for the science of reading.

Abstract: The purpose of this article is to discuss issues of language, specifically African American Vernacular English (AAVE), as it relates to the reading performance of African American children. Previous research on the science of reading provides a research-based framework that is a starting point for evidence-based research that can be used to improve the reading outcomes of African American children. School psychology literature is limited in its inclusion of issues posed by deficit perspectives of AAVE with Bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…The consequences of these narratives are not relegated to the distant past but include contemporary models of education that promote the acquisition of Standardized American English only or be labeled as “at risk” (Yosso, 2005). Latinx and Black psychologists have challenged universalist deficit models of bilingualism by decentering monolingual and monocultural experiences as the normative experience to which all others should be compared (e.g., Higby et al, 2023; Johnson et al, 2023; López et al, 2023). Scholars of color have long challenged racist paradigms and beliefs in the field by deconstructing problematic paradigms (e.g., Black self-hatred; Cross, 1991), reconstructing incomplete accounts of phenomena (e.g., conceptions of peace that ignore racial justice; Azarmandi, 2018), and constructing new theoretical concepts and empirical insights derived from experiences in communities of color (e.g., microaggressions, D. W. Sue & Spanierman, 2020; stereotype threat, Steele, 2011; for further discussion of these approaches, see Cokley & Garba, 2018).…”
Section: Critical History As Antiracist Counterstoriesmentioning
confidence: 99%
“…The consequences of these narratives are not relegated to the distant past but include contemporary models of education that promote the acquisition of Standardized American English only or be labeled as “at risk” (Yosso, 2005). Latinx and Black psychologists have challenged universalist deficit models of bilingualism by decentering monolingual and monocultural experiences as the normative experience to which all others should be compared (e.g., Higby et al, 2023; Johnson et al, 2023; López et al, 2023). Scholars of color have long challenged racist paradigms and beliefs in the field by deconstructing problematic paradigms (e.g., Black self-hatred; Cross, 1991), reconstructing incomplete accounts of phenomena (e.g., conceptions of peace that ignore racial justice; Azarmandi, 2018), and constructing new theoretical concepts and empirical insights derived from experiences in communities of color (e.g., microaggressions, D. W. Sue & Spanierman, 2020; stereotype threat, Steele, 2011; for further discussion of these approaches, see Cokley & Garba, 2018).…”
Section: Critical History As Antiracist Counterstoriesmentioning
confidence: 99%
“…The aforementioned language issues are similar to the context in the United States. For instance, research by speech pathologists have demonstrated that children who speak with high levels of dialect density of African American Vernacular English (AAVE) have slowed literary growth (Graves et al, 2022; Johnson et al, 2022; Puranik et al, 2020). Relatedly, Washington et al (2018) demonstrate that dialect density decreases by about 5% each year of school between kindergarten and second grade, which correlates with an increase in reading comprehension.…”
Section: Assessment Of Black Populations In South Africamentioning
confidence: 99%